Narratives From the 3D Agora-world - Olsen, Sanne Fejfer; Jensen, Sisse Siggaard; Bolander, Klara; Deepwell, Frances; Jones, Chris; Mann, Sarah (Proceedings of the International Conference on Networked Learning, 2004)
This paper is in five narratives based on first hand experiences with 1) being present in a virtual environment (VE) such as the 3D Agora AWEDU presented as an avatar; 2) sensation and communication in avatar based interaction; 3) conventions and the breakdown of conventions in avatar meetings and; 4) knowledge sharing based on reflection-in-(inter)action when exploring and experiencing the VE. The conclusion suggests a concept of “multi-faceted” interaction to be the centre of interest for further research on VEs and avatar meetings.